NIMANN-PICK TYPE C DISEASE. CLINICAL CASE STUDIES - S.V. Mikhailova; E.Yu. Zakharova; T.M. Bukina; D.A. Savin; S.V. Piliya; A.S. Petrukhin (Педиатрическая фармакология)
Nimann-Pick Type C Disease is a hereditary progressive disease of the nervous system from the group of lysosomal accumulation diseases resulting from abnormal subcellular lipid distribution, which leads to the accumulation of cholesterol and glycosphingolipid in the brain and other body tissues. Clinical presentation of the disease is varied and manifested as progressive cerebellar, cognitive disorders, vertical ophthalmoparesis, frequently combined with disorders of the liver, spleen and lungs. This article outlines the key mechanisms of Nimann-Pick type C disease pathogenesis, leading clinical presentations depending on the time the disease manifested it self and key therapy approaches. We described two cases of this disease registered in Russia. It provides a comparative clinical analysis with already published data. To date, a pathogenetic treatment course has been developed for this disease, a timely detection of this pathology is, therefore, important to the burdened family. This representative article on modern data on diagnostics and treatment of NPC is intended for neurologists, pediatricians, psychiatrists and geneticists. Key words: neurodegenerative disease, Nimann-Pick type C disease, convulsions, ataxia, vertical ophthalmoparesis, loss of acquired skills. (Pediatric Pharmacology. – 2010; 7(5):48-53)